APLIKASI CLUSTERING PENGEMBANGAN RESELLER ORDER BERDASARKAN KOTA - Indra Maulana Yusup Kusumah; Sutisna Senjaya; Dedy Apriadi (LPPM STMIK BANDUNG, 2021)
At the Tasshel Convection, resellers are people who sell and buy company products. The reseller sales order data in the tasshel convection is increasingly increasing, besides that this company also has a web-based sales system or order system from resellers. In its sales data, the company has resellers from various cities to sell its products, but the company still has difficulty in developing and increasing product sales. With this problem, it is necessary to create a system that can classify reseller orders by city, which is carried out at the Tasshel Bandung Convection so that this company wants to increase its sales by targeting which cities have the most potential and the opportunity to sell their products by adding resellers or new outlets as a result of many products reaching consumers and the company's sales are increasing and can compete with other companies. The purpose of making an application and analyzing reseller orders for the Tasshel Convection in Bandung City uses the K-Means method. With this application, clustering reseller sales by city in the Tasshel Convection can provide the benefit of the convenience of analyzing reseller order grouping at the Tasshel Convection in Bandung, determining and classifying reseller orders by city. Keywords : K-Means, Clustering, Data Mining, Data Order, Method Waterfall (Classic Life Cycle)